Factors that influence brand loyalty towards brand of smartphone among Generation Y / Syazwani Mohd Salim - Mohd Salim, Syazwani (Faculty of Business and Management, 2019)
This research is about study of factor that would influence the brand loyalty towards brand of smartphone among Generation Y. These includes four independent variables which are brand image, trust, customer satisfaction and promotion that influence the brand loyalty towards the selection brand of smartphone among Generation Y. The survey were conducted at Malacca, Selangor and Sabah. The sample size for this research is 152 respondents. The data collected using questionnaire that distributed at 3 selected area in Malacca, Selangor and Sabah. The researcher will distribute the questionnaire to all respondent who are categorized as Generation Y that are willing to answer the questions. Data are analyzed using reliability test, frequency analysis, descriptive analysis and multiple regression analysis through SPSS Version 24 program. The result show the most influence factors of brand loyalty, the relationship between brand loyalty and brand image, trust, customer satisfaction and promotion and the researcher has gave some recommendations for future researcher to identify the other factor of brand loyalty.